The Great Depression. (Media Rich, 2008)
It was called “Black Tuesday”: the day the bottom fell out of the stock market ushering in the Great Depression. Soon, soup kitchens and breadlines replaced the flappers and speakeasies of the Roaring Twenties. When the nation looked for leadership, they found it in the indelible character and progressive programs of President Franklin Delano Roosevelt, a bright and shining light in the darkness of despair..